2019
DOI: 10.3390/cancers11101509
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Comprehensive Geriatric Assessment as a Predictor of Mortality in Elderly Glioblastoma Patients

Abstract: Background: Treatment of elderly glioblastoma patients (EGP) is a challenge in neuro-oncology. The comprehensive geriatric assessment (CGA) is currently used to assess geriatric oncological patients with other types of tumors. We performed a large retrospective study to analyze its predictive role in EGP. Methods: Patients aged ≥65 years with histologically confirmed diagnosis of glioblastoma were enrolled. CGA included the following tests: the Cumulative Illness Rating Scale-Comorbidity and Severity Index, Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…These assessment tools are not specifically tailored for geriatric populations and do not generally differentiate tumour-related causes from other agerelated causes of impairment. The Comprehensive Geriatric Assessment (CGA), was recently validated as a predictor of mortality in elderly patients with glioblastoma (28) and involves evaluation of neuro-cognitive, functional, nutritional and psychosocial factors; however, the CGA is both time-and resource-intensive and requires training to be properly administered. In a retrospective study of 113 elderly patients with glioblastoma intended to validate the CGA, a large number of patients were medically vulnerable; with a prevalence of frailty of 35%.…”
Section: Determining "Fitness For Treatment" In Elderly Patients With Glioblastomamentioning
confidence: 99%
“…These assessment tools are not specifically tailored for geriatric populations and do not generally differentiate tumour-related causes from other agerelated causes of impairment. The Comprehensive Geriatric Assessment (CGA), was recently validated as a predictor of mortality in elderly patients with glioblastoma (28) and involves evaluation of neuro-cognitive, functional, nutritional and psychosocial factors; however, the CGA is both time-and resource-intensive and requires training to be properly administered. In a retrospective study of 113 elderly patients with glioblastoma intended to validate the CGA, a large number of patients were medically vulnerable; with a prevalence of frailty of 35%.…”
Section: Determining "Fitness For Treatment" In Elderly Patients With Glioblastomamentioning
confidence: 99%
“…Also, in neuro-oncology, there is now at least one trial using a geriatric screening tool in the enrollment phase for elderly patients. Lombardi et al reported a retrospective analysis of a single-center study administering CGA to patients with newly diagnosed GBM and its validation as a predictor of mortality [ 51 ••]. This study included 113 patients aged 65 to 84 years (median 72 years).…”
Section: Geriatric Assessment In Patients With Gliomamentioning
confidence: 99%
“…To date, unfortunately, none of the trials conducted in elderly glioblastoma patients have included geriatric scales like those that are already being applied in the treatment of other cancers. Nevertheless, a recent retrospective study found significant differences in OS when elderly glioblastoma patients were stratified according to a geriatric scale and classified as fit, vulnerable, or frail [ 8 ]. The scales used for other tumors would need to be readjusted for brain tumors and include variables related to neurological function, but once readjusted, they would certainly be useful in determining the best therapeutic option for these patients – not only as regards post-operative treatment but also when deciding on the first neurosurgical approach.…”
mentioning
confidence: 99%